International relations of the Caribbean towards the year 2000. - Bryan, Anthony T. (1990)
Outlines the trends and characteristics of the new and emerging interntional order, brought about by rapid and often unpredictable changes. Summarizes some of the major economic and security factors responsible for uncertainty in the Caribbean, and calls for detailed analysis of the major challenges and opportunities which will be presented to the region, as well as the creation of appropriate mechanisms and policy implementation.